2019
DOI: 10.3390/ma12091390
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Process Parameters and Build Orientation on the Creep Behaviour of a Laser Powder Bed Fused Ni-based Superalloy for Aerospace Applications

Abstract: Additive Layer Manufacturing (ALM) is an innovative net shape manufacturing technology that offers the ability to produce highly intricate components not possible through traditional wrought and cast procedures. Consequently, the aerospace industry is becoming ever more attentive in exploiting such technology for the fabrication of nickel-based superalloys in an attempt to drive further advancements within the holistic gas turbine. Given this, the requirement for the mechanical characterisation of such materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…This can be achieved, for example, by preheating the substrate, as proposed in [ 35 ]. Hot isostatic pressing (HIP) has also been demonstrated to close the cracks as seen from microstructure evaluations [ 13 , 25 , 36 ]. However, the creep life of HIPed L-PBF samples is very low, when compared to cast parts, even after undergoing solutioning and ageing heat treatments [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved, for example, by preheating the substrate, as proposed in [ 35 ]. Hot isostatic pressing (HIP) has also been demonstrated to close the cracks as seen from microstructure evaluations [ 13 , 25 , 36 ]. However, the creep life of HIPed L-PBF samples is very low, when compared to cast parts, even after undergoing solutioning and ageing heat treatments [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presented thermal treatment modes were selected based on the analysis of the literature in terms of the effect of thermal treatment on the mechanical properties of metals manufactured by AM [22][23][24][25][26][27][28][29]. The authors of [26] found that the creeping flow properties of IN718 samples alongside the 3D printing direction were better compared to those alongside the scanning direction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] This potential has been exploited in a plethora of areas, like economy, [ 2 ] education, [ 3 ] and, in especial, it has contributed to a new perspective in materials science. [ 4–6 ] One of the interests of this field is to improve and/or to tune the mechanical properties of materials for applications in automotive, [ 7,8 ] aerospace, [ 9 ] civil, [ 10 ] and biomedical [ 11 ] fields, among others. In this sense, nature is a good source of inspiration, where we have many examples that structures, shapes, topologies, and hierarchical geometrical designs are parameters of fundamental importance to determine the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%